2019
DOI: 10.1093/mnras/stz3518
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the companion AGBs using surface chemical composition of barium stars

Abstract: Barium stars are one of the important probes to understand the origin and evolution of slow neutron-capture process elements in the Galaxy. These are extrinsic stars, where the observed s-process element abundances are believed to have an origin in the now invisible companions that produced these elements at their asymptotic giant branch (AGB) phase of evolution. We have attempted to understand the s-process nucleosynthesis, as well as the physical properties of the companion stars through a detailed compariso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 117 publications
(135 reference statements)
2
44
0
Order By: Relevance
“…We concluded that the metallicity is the best predictor of the sprocess pattern, with lower metallicities favouring the production of the elements of the second peak relative to the first peak, as observed in the Ba stars. This results appear to be confirmed by recent observations of 10 Ba stars (Shejeelammal et al 2020).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…We concluded that the metallicity is the best predictor of the sprocess pattern, with lower metallicities favouring the production of the elements of the second peak relative to the first peak, as observed in the Ba stars. This results appear to be confirmed by recent observations of 10 Ba stars (Shejeelammal et al 2020).…”
Section: Introductionsupporting
confidence: 92%
“…The models have high δ values, but as for CPD −64 • 4333, the short orbital period of the system could explain this phenomenon. Shejeelammal et al (2020) also analysed this star and found an initial AGB mass of 2.5 M ⊙ based on χ 2 minimalisation using FRUITY models. They have found [Fe/H] = −0.5 and generally higher s-process abundances than the data in this study.…”
Section: Hd211594mentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies revealed that the [Rb/Fe] ratio tends to be moderately supersolar (0≲ [Rb/Fe] ≲ 0.5) at the metal‐poor regime ([Fe/H] ≲ −1). Successively, Rb abundances of globular cluster giants (D'Orazi et al 2013; Yong et al 2006, 2008) or AGB giants (García‐Hernández et al 2006; Shejeelammal et al 2020) were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…TAKEDA Successively, Rb abundances of globular cluster giants (D'Orazi et al 2013;Yong et al 2006Yong et al , 2008 or AGB giants (García-Hernández et al 2006;Shejeelammal et al 2020) were also investigated.…”
mentioning
confidence: 99%